Evaluation of the CAN SPAM Act: Testing Deterrence and Other Influences of E-mail Spammer Legal Compliance Over Time. (August 2015) - Kigerl, Alex C.
E-mail spam has been growing since its inception. The Controlling the Assault of Non-Solicited Pornography and Marketing Act (CAN SPAM Act) is U.S. federal legislation that was passed in response to the growing spam problem. A series of evaluations followed after the Act, most of which reported that compliance with the Act's requirements among spammers had not been affected. However, none of these evaluations used methods that were sufficiently rigorous, failing to capture the continuous nature of CAN SPAM Act's enforcement, using a limited number of measures of noncompliance, and ignoring a variety of possible spurious influences. This research addresses all of these limitations by analyzing a sample of 5, 490, 905 spam e-mails sent between 1998 and 2013. Ten measures of spammer compliance with the CAN SPAM Act were operationalized to test the impact the Act had. Thirteen measures of CAN SPAM Act enforcement were coded from news articles and included in a time-series regression. Findings suggest that the Act may in fact be a deterrent, but in such a way as to increase CAN SPAM Act violations of header forgery as a precaution against being caught.